POLITICAL WILL PEMERINTAH KABUPATEN KAMPAR TERHADAP PEMBANGUNAN DESA SANGAT TERTINGGAL TAHUN 2022 - Yulia, Rischa; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Rural development requires involvement between the government and the community from planning to implementation of the development. The commitment to equitable development between regions is included in the policy of accelerating the development of underdeveloped regions. Based on data from the Village Development Index, the number of very underdeveloped villages in Kampar Regency in 2022 is 23 villages, the majority of which are in Kampar Kiri Hulu District. Therefore, this study aims to determine the political will of kampar district government towards the development of very underdeveloped vilage in 2022. This study uses a descriptive qualitative approach with data collection techniques including interview and documentation techniques. Then, the data analysis technique uses a qualitative descriptive analysis technique which includes data collection, data reduction, data presentation and drawing conclusions. The location of this study is in Kampar Regency, Riau Province. This study uses the political will theory from Brinkerhoff (2010), to determine political will consisting of several indicators. The indicators are government initiatives, priority policy/program choices, mobilization of parties, public commitment and resource allocation, business sustainability, and learning and adaptation. The results of this study indicate that Will of the Kampar Regency Government for the Development of Very Underdeveloped Villages in 2022 is still not optimal. Essentially, the implementation of development programs in the Kampar Regency Medium-Term Development Plan (RPJMD) for 2017-2022 is still not optimal due to limited funding sources and the lack of collaboration between the government and third parties. The Kampar Government's efforts to eliminate the status of very underdeveloped villages and increase them to developing villages are by intervening in the IDM value. Keywords: Political Will, Development, Very Underdeveloped Village